ANALISIS TERHADAP PERTIMBANGAN HUKUM PUTUSAN HAKIM PENGADILAN AGAMA DALAM PERMASALAHAN SYARAT-SYARAT POLIGAMI (Analisis Pasal 4 Ayat (2) UU Nomor 1 Tahun 1974 Tentang Perkawinan) - QOMARONI, QOMARONI (Dinamika Hukum, 2016)
The purpose of this study 1). know the basic legal considerations in decisions Religious Court case for a license poligami.2) .mengetahui consideration of the judge waive the provisions of terms polygamy set out in Article 4 (2) of Law No. 1 of 1974, 3) .mengetahui whether Article 4 (2) of Law No. 1 of 1974 is still relefan with a sense of justice in society, or is not in accordance with the legal norms of living in society. The background problem that Act No. 1 of 1974 is already 41 years old, in its application in the Religious often overlooked by the judges in a decision Hank dropped, particularly Article 4 (2). The existence of such article by some judges considered to have no power to and does not reflect a sense of justice in society. The research method consists of, kind of normative juridical research, the necessary data is secondary data including primary legal materials such as Law No. 1 of 1974 on Marriage and Religious Court several decisions about Polygamy License Application. In addition, secondary law such as the results of research and expert opinion is relevant. While tertiary legal materials used are Indonesian dictionary, legal dictionary, encyclopedia. The results showed that Court Judge Religion in decisions about the case for a license polygamy tend to use the legal considerations of the religion professed and believed by the parties and the laws that live in the community and run by the communities themselves, while also considering the aspects of benefit and kemadhorotannya for family parties, so that although the reasons for the request polygamy filed by the applicant (husband) to the Religious Courts do not comply with the terms of polygamy set out in article 4, paragraph (2) of Law No. 1 of 1974 still granted by the Religious Courts. Keywords: legal considerations, religious courts, polygamy